2007
DOI: 10.1016/j.jeurceramsoc.2006.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Densification during hot-pressing of carbon nanotube–metal–magnesium aluminate spinel nanocomposites

Abstract: The densification by hot-pressing of ceramic-matrix composites containing a dispersion of carbon nanotubes (CNT), mostly single-walled, is studied for the first time. Fifteen different CNT-Co/Mo-MgAl 2 O 4 composite powders containing between 1.2 and 16.7 vol.% CNT were prepared by catalytic chemical vapour deposition. The in situ growth of CNT within the oxide powder made it possible to obtain a highly homogeneous distribution of CNT. Low contents of CNT (up to 5 vol.%) are beneficial for the first shrinkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 28 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…One of the first studies on synthesis of CNT/ceramic composites (published in two parts) was authored by Peigney and co-workers 39,40 [41][42][43][44][45][46][47][48] . These composite powders can then be hot pressed to form macroscopic composites.…”
Section: In-situ Growth Of Cnts By Chemical Vapour Decomposition (Cvd)mentioning
confidence: 99%
“…One of the first studies on synthesis of CNT/ceramic composites (published in two parts) was authored by Peigney and co-workers 39,40 [41][42][43][44][45][46][47][48] . These composite powders can then be hot pressed to form macroscopic composites.…”
Section: In-situ Growth Of Cnts By Chemical Vapour Decomposition (Cvd)mentioning
confidence: 99%
“…11 Another explanation is given by Peigney et al who attribute the increased grain rearrangement to the fact that CNTs facilitate sliding at grain contacts and therefore to a lower friction coefficient between grains. 12 As a consequence the grain rearrangement densification mechanism will be increased. The second decrease in densification rate can be related to the formation of a rigid network of MWCNT providing a sintering constraint.…”
Section: Densification Of Freeze Dried Powder Mixtures By Hot Pressingmentioning
confidence: 99%
“…Other authors attribute the decrease in shrinkage in the longitudinal direction to a decrease in shear stresses in the longitudinal direction, redistributing the stresses in the transversal direction, and therefore inhibiting plastic flow. 12 Hot pressing of alumina-CNT nanocomposites has been studied by several authors. 14-16 It is not easy to compare the results of this study with those found in literature as…”
Section: Densification Of Freeze Dried Powder Mixtures By Hot Pressingmentioning
confidence: 99%
“…4 In the last few years new ceramic/carbon nanotube composites have been developed and a number of authors have reported improved mechanical and functional properties in the case of ceramic/CNT composites compared to the monolithic material. [7][8][9][10][11] Three main problems have been recognized during these investigations; dispersion of the CNTs in the matrix, 12 densification of the composites and degradation of the CNTs. Conventional mixing of CNTs with the matrix powder requires long milling times which may damage the CNTs.…”
Section: Introductionmentioning
confidence: 99%